2021
DOI: 10.3389/fphar.2021.747075
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Incidence, and Prognosis of Thromboembolism in Cancer Patients Treated With Immune Checkpoint Inhibitors

Abstract: In recent years, immune checkpoint inhibitors (ICIs) have become the standard treatment option for tumors. With the widespread application of ICIs, immune-related adverse events (irAEs) have gradually attracted the attention of researchers. Owing to the characteristics of ICIs, irAEs can affect each organ of the human body. Thromboembolism is uncommon in cancer patients receiving ICIs, but it may affect their survival. Most thromboembolic events do not cause serious effects after early prediction and treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…MDSCs can promote platelet aggregation. Also, through CXCR1/MDSCs, induce tumor to release Neutrophil Extracellular Traps (NETs) which play a significant role in thrombosis [84].…”
Section: The Role Of Platelets In Immunity Inflammation and Iraesmentioning
confidence: 99%
“…MDSCs can promote platelet aggregation. Also, through CXCR1/MDSCs, induce tumor to release Neutrophil Extracellular Traps (NETs) which play a significant role in thrombosis [84].…”
Section: The Role Of Platelets In Immunity Inflammation and Iraesmentioning
confidence: 99%
“…In the current study, we observed a trend toward a higher lethality rate of venous embolism and thrombosis when ICIs and VEGFIs were used together compared with their individual use. The mechanisms involved in the increased frequency of thromboembolism with ICIs remain unclear but include increased tissue factor production in monocytes associated with T-cell activation (Zou et al, 2021). In addition, a higher risk of venous thromboembolism has been reported in patients with c-reactive protein flares early after ICI administration (Moik et al, 2022), and increased secretion of various cytokines associated with inflammatory responses may contribute to coagulation abnormalities.…”
Section: Figurementioning
confidence: 99%
“…Thrombotic complications in cancer patients are common [30,31] and are denominated cancer-associated thrombosis (CAT), but their risk can be influenced by the therapy applied [32][33][34]. Some studies analyzed the relationship between thromboembolic events and ICI treatment in NSCLC patients, showing, for the first time, that the risk of thrombosis is not negligible [33,[35][36][37][38][39]. Further research is needed to discover precise mechanisms underlying the interaction of hemostasis, immunological response and cancer in the context of ICI therapy [29].…”
Section: Introductionmentioning
confidence: 99%